Hydroponics gel as a new electrolyte gelling agent for alkaline zinc–air cells - Othman, Raihan; Basirun, Wan Jefrey; Yahaya, Abdul Hamid; Mohd Arof, Abdul Kariem (Elsevier, 2001)
The viability of hydroponics gel as a new alkaline electrolyte gelling agent is investigated. Zinc–air cells are fabricated employing 12 wt.% KOH electrolyte immobilised with hydroponics gel. The cells are discharged at constant currents of 5, 50 and 100 mA. XRD and SEM analysis of the anode plates after discharge show that the failure mode is due to the formation of zinc oxide insulating layers and not due to any side reactions between the gel and the plate or the electrolyte.